An overview of time and cost in arbitration for construction projects / Azira Ibrahim ... [et al.] - Azira, Ibrahim; Zulhabri, Ismail; Thuraiya, Mohd; Ida Nianti, Mohd Zin (2015)
Arbitration is one of the dispute resolution widely used in construction industries. Most of the construction contracts provide the arbitration clause to give the contractual parties a way out to settle the dispute. Most of the contractual parties have chosen arbitration in their dispute for two good reasons. Arbitration provides quicker decision making process than litigation. The second reason contractors choose arbitration because it will provide them arbitrator with much experience in the construction industry. In arbitration, the final award granted by an arbitrator will be classified as private and confidential. As a result the award given will be kept as a secret unless the permission is givenfrom the dispute parties. The issue here is once the proceedings are classified as private and confidential, the potential dispute parties do not know the time taken to settle the dispute and also the cost involved in arbitration proceedings. Only the disputed parties know how much they need to spend in order to settle the dispute and how long the time is needed for the whole process of arbitration. Therefore the objectives of this research are; to identify the current arbitration time frame to complete the proceedings by referring to case studies; to determine the relevant costs incurred in the arbitration proceeding by referring to the rules imposed by relevant bodies; and lastly to develop a framework relevant to time and cost in arbitration proceedings. To achieve the objectives of this study, data collection through content analysis technique will be applied to analyse selected case studies. In addition, in depth interview with an arbitrator and relevant stakeholders who experienced in arbitration proceedings will be arrange in order to answer research objectives.